The subjects of the offenses to the norms on safety and health at work and the social and organizational effects specific to companies conducting mining activities - Popescu, Ioan; Lohan, Nicoleta-Monica; Baciu, Constantin; Cazac, Alin-Marian; Baciu, Elena-Raluca (MATEC web of conferences, 2020)
The offenses concerning safety and health at work have no material object, their constitutive content including: the object and subject of the offense, the objective and subjective side of the offense. The active subjects of an offense have a legal obligation to apply and control the implementation of occupational safety and health measures and the passive subjects will bear the consequences of the occurrence of specific events. The existence of some uncertainties in the current legislation, also affecting mining companies, creates legal disputes especially in relation to the issues concerning active subjects. As for the passive subjects, the legal loophole refers to the situation of the day-labourers who may be involved in accidents at work and occupational illnesses. The authors consider it is necessary to formulate new law articles for clarification and even to draw up a future law with concrete reference to day-labourers, but also to some new risk sensitive social groups. Thus, the egal work relationships: the manner of performing the work, its remuneration and subordination to the beneficiary carrying out mining activities, will also be specified.